Relevansi Tri Kaya Parisudha dalam Penguatan Profil Pelajar Pancasila di Sekolah Abad ke-21 - Sukrini, Ni Made (Satya Widya: Jurnal Studi Agama, 2025)
This study aims to analyze the relevance and implementation strategies of the Tri Kaya Parisudha values (Manacika, Wacika, Kayika) in strengthening the Indonesian national character framework known as the Profile of Pancasila Students. Using a qualitative approach through observation, interviews, and document analysis, the study reveals that Tri Kaya Parisudha has a strong philosophical and pedagogical connection to the six dimensions of the Pancasila Student Profile. However, its implementation in schools remains sporadic and is not systematically integrated into learning processes. Teachers tend to perceive Tri Kaya Parisudha merely as a component of Hindu Religious Education rather than as universal ethical principles applicable across subjects. Additional challenges include the lack of moral-reflection practices, weak digital moral literacy, and school cultures that do not fully support character habituation. The study recommends integrative strategies such as developing teaching modules based on Tri Kaya Parisudha, implementing problem-based and project-based learning, moral dialogues, reflective practices, and strengthening digital ethics. The findings indicate that Tri Kaya Parisudha not only supports moral development but also enhances critical thinking, ethical communication, creativity, responsibility, and collaboration—competencies essential for 21st-century learning. Overall, the study affirms that Tri Kaya Parisudha has strong potential as a local wisdom–based character education